Use of a polyanionic carbomer, Carbopol971P, in combination with MF59, improves antibody responses to HIV-1 envelope glycoprotein - Dey, Antu K. (2012)
Identification of optimal antigen(s) and adjuvant combination(s) to elicit potent, protective, and long-lasting immunity has been a major challenge for the development of effective vaccines against chronic viral pathogens, such as HIV-1, for which there are not yet any licensed vaccines. Here we describe the use of a novel adjuvant approach employing Carbopol 971P(®) NF (hereafter referred to as Carbopol971P), a cross-linked polyanionic carbomer, in combination with the Novartis proprietary oil-in-water adjuvant, MF59, as a potentially safe and effective adjuvant to augment humoral immune responses to the HIV-1 envelope glycoprotein (Env). Intramuscular immunization of small animals with recombinant Env glycoprotein (gp140) formulated in Carbopol971P plus MF59 gave significantly higher titers of binding and virus neutralizing antibodies as compared to immunization using gp140 with either MF59 or Carbopol971P alone. In addition, the antibodies generated were of higher avidity. Importantly, the use of Carbopol971P plus MF59 did not cause any serious adverse reactions or any obvious health problems in animals upon intramuscular administration. Hence, the Carbopol971P plus MF59 adjuvant formulation may provide a benefit for future vaccine applications.